‘Young Rovers’ and ‘Dazzling Lady Meteors:’ Gender and Bicycle Club Culture in Turn-of-the-Century Small-Town Ontario - Beausaert, Rebecca (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2013)
During the bicycle “craze” of the 1890s and early 1900s, men and women across Western Europe and North America embraced this novel form of recreation and modern mode of transportation. Undoubtedly, the invention of the “safety” bicycle in 1885 aided women’s enjoyment of the machine, yet in many respects cycling remained an androcentric mode of recreation. This is most evident when examining the paternal structure of bicycle clubs. In the existing literature on cycling, however, little attention is paid to gender dynamics within clubs, especially in the context of smaller towns and rural areas. Using the towns of Tillsonburg and Ingersoll in southwestern Ontario’s Oxford County as a case study, this article examines how cycling clubs in these communities were sites of both change and resistance to the prevailing gender norms of the time. Once membership was opened to women, club activities became more heterosocial and less focused on cultivating virulent masculinity, but women were never fully accepted as full-fledged members.